Finding consciousness in the brain : a neurocognitive approach - Grossenbacher, Peter G. (Advances in consciousness research, 2001)
How does the brain go about the business of being conscious? Though we cannot yet provide a complete answer, this book explains what is now known about the neural basis of human consciousness. The last decade has witnessed the dawn of an exciting new era of cognitive neuroscience. For example, combination of new imaging technologies and experimental study of attention has linked brain activity to specific psychological functions. The authors are leaders in psychology and neuroscience who have conducted original research on consciousness. They wish to communicate the highlights of this research.